Internet marketing - Agustin-Acierto, Marife; Acierto, Gilfred Abad; Gordonas, Annabelle, editor (Manila : Unlimited Books Library Services & Publishing Inc., 2022)
"This book elaborates the world of retailing and e-tailing. It fills the gap for those who have found Internet Marketing studies. It sustains information which lacks from too much 'E' and less on marketing or are two narrowly or have difficulty on e-commerce. It discusses the basic marketing and explores key marketing concepts in the context of today's digital/Internet environment. The book introduces the uses of the Internet. E-marketing strategy and web page development skills can largely help readers of this book.
Includes references.
English.
Keywords: Internet marketing